“AND WHAT DOES ANYTHING AT ALL MATTER?”: Asceticism and the Hermeneutics of Comfort in Hopkins’s Terrible Sonnets - Yost, Julia Dorothy (2014)
On one account, the life and work of Gerard Manley Hopkins reveal Catholic asceticism as a grim, life-denying regimen, a form of ethical extremism inimical to the poet’s psychological comfort and his creativity. In Hopkins’s latter years, runs the logic, stringent self-denial conduced to depression and to poetic chastening, with the so-called Terrible Sonnets exemplifying both. This essay, however, contends that Hopkins’s asceticism implemented a hermeneutic productive of both psychological recuperation and literary ingenuity. What Hopkins sought was “comfort” in an archaic sense of that word, as goal-oriented and ethical. Such comfort, as the set of objects and affects associated with asceticism, is thematized throughout the Terrible Sonnets. Tracing the theme will serve to draw out the recuperative hermeneutic of Hopkins’s asceticism, which redeems Hopkins’s life in Dublin and establishes the consistency of these late sonnets with his seemingly more characteristic earlier work.
Keywords: Gerard Manley Hopkins -- Terrible Sonnets -- asceticism -- Tractarianism